In situ occurrence and conservation of Beta vulgaris subsp. maritima ((L.) Arcangeli) in Italy - Zucchini, Cecilia; Raggi, Lorenzo; Grassi, Anna; Spataro, Giorgia; Gigante, Daniela; Negri, Valeria (Frontiers in Ecology and Evolution, 2024)
IntroductionCrop Wild Relatives (CWR) have great socioeconomic importance for humans harbouring a broad spectrum of diversity and being important elements of different habitats. Beta vulgaris subsp. maritima ((L.) Arcangeli), also known as sea beet, is an important CWR of cultivated beets (GP-1). The high adaptability of this taxon to different environmental conditions, as well as its tolerance/resistance to different biotic and abiotic stresses, makes it a vital source for sugar beet improvement. Aim of this work was to analyse the in situ and ex situ status of sea beet population conservation in Italy, so as to guide protection activities and new collecting missions.MethodsGeographical distribution data of populations were that occur in the wild and conserved in genebanks were assembled from different databases and submitted to data quality control. Distribution, habitat characterization, land cover and use of the involved sites were then evaluated to provide insight into the current condition of areas hosting this CWR diversity. The presence of populations within vs. outside Italian protected areas was also evaluated. A density analysis of the records was performed and the adequateness of sea beet ex situ conservation, in terms of number of conserved accessions, was finally estimated.ResultsA collection of 138 B. vulgaris subsp. maritima high quality georeferenced records were obtained, mainly distributed into Mediterranean Biogeographic Region. About 22% of the considered populations occurs in protected sites of the Natura 2000 Network, while about 15% in areas recorded in the Official list of protected natural areas (EUAP). Occurrences within protected areas are founded primarily in natural environments, whereas those outside are mainly located in urban and cultivated areas. The comparison of distribution and density analysis results revealed the presence of several gaps between sites hosting in situ populations and sites where ex situ conserved accessions were originally collected.DiscussionHere presented data indicates that the protection status for sea beet in Italy can be considered only partially adequate; more proactive protection measures should be foreseen to increase the role of protected areas in safeguarding in situ conservation. “Out of reserve management” for populations outside protected areas should also be developed, as well as new collecting missions carried out.